Pseudoaneurysm of the uterine artery with presentation of haematuria; a rare case report. (January 2022) - Anwer, Majid; Kumar, Anil; Kumar, Anurag; Kumar, Subhash; Kumar, Deepak; Ahmed, Farheen
Abstract: Introduction: Pseudoaneurysm of the uterine artery is a condition in which extra luminal collection of blood with a turbulent flow that communicates with flowing blood of uterine artery through a defect in its arterial wall. As per literature uterine artery pseudoaneurysm is a very rare condition and its incidence is 2–3/1000 deliveries. Clinical diagnosis is very challenging and in the index case haematuria was the presenting complaint which in fact is the extremely rare presenting complaint. Angioembolization is the ideal treatment modality for such a rare condition. Case presentation: A 25-year old female presented in a shock state with history of massive haematuria two months after delivering a baby. She was resuscitated with fluid, blood and blood products. A computed tomography angiogram was done which showed a large pseudoaneurysm of the left uterine artery so consequently angioembolization was done with n-butyl cyanoacrylate (NBCA) and lipoid mixture. Serial assessment of biochemical and clinical parameters depicted improvement in the clinical status of the patient. She was doing well at 6 months of follow up. Discussion: A post-partum massive haematuria could be due to pseudo aneurysm of uterine artery. The presentation of haematuria may occur due to communication of aneurysm with urinary bladder and which further get ruptured. Aggressive resuscitation and angioembolization of the pseudoaneurysm is employed to treat such patients. Conclusion: Pseudoaneurysm of uterine artery is rare condition which may present as haematuria. Once clinical diagnosis is suspected it's better to first resuscitate and plan for angioembolization for better outcome. Highlights: Pseudoaneurysm of uterine artery presented with haematuria is the first case to be reported in the leterature. Clinically the pseudoaneurysm of uterine artery should be considered in mind in patients with massive haematuria after caesarean/normal deliveries. Aggressive resuscitation and definitive management with embolization is the ideal treatment for such cases.